Comparing the poverty-reduction efficiency of targeted versus universal benefits amid crises - Adnan Shahir; Ravi Kanbur; Jukka Pirttilä; Pia Rattenhuber (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This study evaluates which type of benefit-a universal benefit, a proxy mean-tested benefit, or a categorical benefit- better cushions the poverty effects of income shocks in a developing economy. We compare the effectiveness of the three benefit schemes on poverty first conceptually and then by considering two different crisis scenarios, the COVID-19 pandemic and a hypothetical agricultural shock, in a tax-benefit microsimulation model for Ethiopia. The results suggest that while the proxy-means-tested benefits are the most effective in reducing the poverty gap index, a simple categorical benefit is equally good in lowering the headcount poverty. Universal benefits may lead to lower poverty increases when crises hit. This suggests that there could be a trade-off between minimizing poverty during normal times and offering protection against shocks when the poverty incidence changes.
Keywords: C81; D31; H55; I32; 330; social protection; income distribution; poverty; microsimulation; COVID-19; Ethiopia